Real-world treatment and retreatment patterns and outcomes in patients with advanced or metastatic non-small cell lung cancer following nivolumab monotherapy in second line or later in France: an I-O Optimise analysis - Justeau, Grégoire; Chouaid, Christos; Debieuvre, Didier; Audigier-Valette, Clarisse; Quantin, Xavier; Léna, Hervé; Bosquet, Lise; Girard, Nicolas; Schoemaker, Minouk J.; Mella, Marta; Pinto Correia, Bárbara; Rault, Caroline; et al. (Frontiers in Oncology, 2025)
IntroductionThis study describes treatment and retreatment patterns and outcomes in patients in France following nivolumab as a second-line or later (2L+) treatment in locally advanced or metastatic non-small cell lung cancer (LAM NSCLC).Materials and methodsThis analysis included adults with tumor, node, metastasis stage IIIB–IV NSCLC (as defined in the 7th or 8th edition American Joint Committee on Cancer/Union for International Cancer Control) treated with nivolumab monotherapy in 2L+ using data from the retrospective Epidemiological-Strategy and Medical Economics Lung Cancer database. The inclusion period was from January 1, 2015, to September 30, 2020, with a follow-up until September 30, 2021. Analyses were stratified according to the duration of index nivolumab treatment and tumor programmed death ligand 1 expression levels.ResultsIn total, the study included 4,001 patients (68% male; mean age [standard deviation] at index date, 63.6 [9.7] years) with a median follow-up of 34.3 months. The median nivolumab duration was 2.5 months (interquartile range, 1.4–6.3). The median overall survival (OS) from nivolumab initiation was 10.2 months (95% confidence interval [CI], 9.6–10.8). The median real-world progression-free survival and time to treatment discontinuation or death (95% CI) were 2.2 (2.1–2.3) and 2.7 (2.5–2.8) months, respectively. In total, 2,985 (74.6%) patients discontinued index nivolumab treatment: 226 (7.6% of discontinuers) received a further immune checkpoint inhibitor (ICI; 12.3% of discontinuers receiving further systemic treatment), and 1,604 (53.7%) received chemotherapy and/or targeted therapy. The proportion of ICI-retreated patients was the highest among those with the longest index treatment duration (15.8% among discontinuers receiving ≥26 weeks’ index nivolumab). The median OS from retreatment was longer in the resumption (ICI restart without another therapy for ≥6 weeks) compared with the rechallenge (ICI restart following non-ICI therapy) patient subgroup.ConclusionFew patients with LAM NSCLC in France received ICI retreatment following index nivolumab discontinuation, but the proportion increased with a longer duration of index nivolumab.